The Intertextuality and Proverbs in the Messages of Badi Al-Zaman Al-Hamathani (D398A.H) - Mousa, علاء الدين زكي علي; Alseoudi, نزار جبريل إبراهيم; Alsharef, علي كامل علي (Dirasat: Human and Social Sciences, 2023)
Objectives: Despite the meticulous care given to his shrines, Badi' Al-Zaman's letters, showcasing his rhetorical and stylistic prowess, have received insufficient critical attention. This study explores Badi Al-Zaman Al-Hamdhani's letters through an intertextual lens, highlighting their semantic and aesthetic dimensions. Methods: Employing a critical inductive approach, the study linguistically, rhetorically, and semantically analyzed all proverbs in Bedi Al-Zaman's missionary texts within their contexts. It deconstructed and examined the proverbs for cultural dimensions and implications, constructing a comprehensive critical scene encompassing all dimensions and contents. Statistical methods and balancing tools were applied to compare proverbs in one case, while in another, Bedi Al-Zaman's letters were compared. Results: In this study, the letters of Badi Al-Zaman revealed intertextuality in all three types: the direct intertextuality (the intertextuality of manifestation), the indirect intertextuality (the intertextuality of transformation), and the intertextuality of absorption and absorption (the intertextuality of invisibility). Moreover, it gave rise to a variety of intertextual manifestations mechanisms such as: elongation, intensification, and reduction, and the forms that derive from it: such as anakram, parakram, and allusion. The study showed that types of intertextuality and their mechanisms played a role in transforming epistolary texts into dynamics of reading and broadening horizons. Conclusions: Analyzing Intertextuality and proverbs in Badi Al-Zaman's letters unveils his profound artistic maturity. Recognizing the intertextuality of his letters confirms his full literary awareness, especially of proverbs, showcasing his ability to revive them uniquely.